1993
DOI: 10.1128/jcm.31.4.887-894.1993
|View full text |Cite
|
Sign up to set email alerts
|

Determination of carbohydrate profiles of Bacillus anthracis and Bacillus cereus including identification of O-methyl methylpentoses by using gas chromatography-mass spectrometry

Abstract: BaciUus anthracis and BaciUus cereus are closely related pathogenic organisms that are difficult to differentiate phenotypically or genotypically. It is well known that vegetative and spore forms of bacilli are quite distinct both morphologically and chemically, but spore-specific chemical markers allowing these species to be distinguished have not been previously described. By using gas chromatography-mass spectrometry, vegetative cells and spores of the two species were shown to exhibit distinct carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Using two specific carbohydrate binding lectins, wheat germ agglutinin (WGA) and concanavalin A (Con A), as probes, we show that the carbohydrates N-acetylglucosamine (GlcNAc) and glucose/mannose (Glu/Man) can be detected, mapped and quantified on single entire bacterial cell surfaces at the nanoscale. The choice of these targets was dictated by several studies showing the heterogeneity and changes in aminosugar and simple sugars across different strains and species, making them critical targets for profiling [1,7,11,12]. We show that these carbohydrates can be measured in both vegetative and spore states in liquid environments.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Using two specific carbohydrate binding lectins, wheat germ agglutinin (WGA) and concanavalin A (Con A), as probes, we show that the carbohydrates N-acetylglucosamine (GlcNAc) and glucose/mannose (Glu/Man) can be detected, mapped and quantified on single entire bacterial cell surfaces at the nanoscale. The choice of these targets was dictated by several studies showing the heterogeneity and changes in aminosugar and simple sugars across different strains and species, making them critical targets for profiling [1,7,11,12]. We show that these carbohydrates can be measured in both vegetative and spore states in liquid environments.…”
Section: Introductionmentioning
confidence: 94%
“…Owing to their ability to form spores in response to nutrient deprivation conditions, the profiles of both vegetative cells and spores for these bacilli have been of great interest [11]. Changes in the surface carbohydrate compositions on B. anthracis and B. cereus were investigated as surface biochemical markers for tracking the spore-forming process [12]. To date, several techniques have been applied to analyse the bacterial surface carbohydrate compositions, primarily involving the use of gas chromatography-mass spectrometry (GC-MS), ion-exchange chromatography, gel chromatography and high-performance liquid chromatography [1,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…As there are no stains for specific anionic groups, the images were interpreted with reference to previous studies (Driks 1999;Waller et al 2004). For example, it has been reported that the outer surface of the exosporium surrounding B. anthracis and Bacillus subtilis spores contains glycoproteins (Fox et al 1993;Fox et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…2004). For example, it has been reported that the outer surface of the exosporium surrounding B. anthracis and Bacillus subtilis spores contains glycoproteins (Fox et al. 1993; Fox et al.…”
Section: Discussionmentioning
confidence: 99%
“…There is clearly a need for further study of the carbohydrate contents of brucellae. Whole-cell carbohydrate profiling by gas chromatography-mass spectrometry (GC-MS) has proven successful in differentiating other closely related groups of organisms, including legionellae and bacilli (12,14,15,34).…”
mentioning
confidence: 99%